Results from Ad Hoc and Routinely Collected Data among Celiac Women with Infertility or Pregnancy Related Disorders: Italy, 2001–2011. (7th May 2014) - Fortunato, Francesca; Martinelli, Domenico; Prato, Rosa; Pedalino, Biagio
Abstract : Celiac disease (CD) is a chronic autoimmune illness triggered by gluten consumption in genetically predisposed individuals. Worldwide, CD prevalence is approximately 1%. Several studies suggest a higher prevalence of undiagnosed CD in patients with infertility. We described reproductive disorders and assessed the frequency of hospital admissions for infertility among celiac women aged 15–49. We conducted two surveys enrolling a convenient sample of celiac women, residing in Apulia or in Basilicata (Italy). Moreover, we selected hospital discharge records (HDRs) of celiac women and women with an exemption for CD, and matched the lists with HDRs for reproductive disorders. In the surveys we included 91 celiac women; 61.5% of them reported menstrual cycle disorders. 47/91 reported at least one pregnancy and 70.2% of them reported problems during pregnancy. From the HDRs and the registry of exemption, we selected 4, 070 women with CD; the proportion of women hospitalized for infertility was higher among celiac women than among resident women in childbearing age (1.2% versus 0.2%). Our findings highlight a higher prevalence of reproductive disorders among celiac women than in the general population suggesting that clinicians might consider testing for CD women presenting with pregnancy disorders or infertility.